2021
DOI: 10.1002/1878-0261.13094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical potential of circulating free DNA and circulating tumour cells in patients with metastatic non‐small‐cell lung cancer treated with pembrolizumab

Abstract: Immune checkpoint inhibitors (ICIs), such as pembrolizumab, are revolutionizing therapeutic strategies for different cancer types, including non-small cell lung cancer (NSCLC). However, only a subset of patients benefits from this therapy, and new biomarkers are needed to select better candidates. In this study, we explored the value of liquid biopsy analyses, including circulating free DNA (cfDNA) and circulating tumour cells (CTCs), as a prognostic or predictive tool to guide pembrolizumab therapy. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 75 publications
3
20
1
Order By: Relevance
“…They showed that improved response to therapy correlated with lower nucleosome levels before the second and third cycle of chemotherapy, independent of other confounders [ 129 ]. Various other groups have in turn shown cfDNA levels predict limited response to chemotherapy and immunotherapy in various cancers [ 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. This human data is notable since it suggests a pan-cancer clinical association between elevated cfDNA and limited therapeutic response.…”
Section: Clinical Relevance Of Nets In Resistance To Cancer Therapymentioning
confidence: 99%
“…They showed that improved response to therapy correlated with lower nucleosome levels before the second and third cycle of chemotherapy, independent of other confounders [ 129 ]. Various other groups have in turn shown cfDNA levels predict limited response to chemotherapy and immunotherapy in various cancers [ 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. This human data is notable since it suggests a pan-cancer clinical association between elevated cfDNA and limited therapeutic response.…”
Section: Clinical Relevance Of Nets In Resistance To Cancer Therapymentioning
confidence: 99%
“…Thus, despite the few known driver mutations found in SCLC, cfDNA quantification allows to quantify the total levels before treatment and monitor the changes during therapy. Recently, our group demonstrated the feasibility to quantify cfDNA levels in non-small cell lung cancer patients and its association with patients’ outcomes (45), suggesting its possible utility in SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both methods could be used to robustly measure the cfDNA content. However, to complete our study we chose the qPCR assay, which is a high sensitive and specific assay for cfDNA quantification in SCLC patients, and was previously employed in studies focused on non-small cell lung cancer (4548).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CRC patients with positive postsurgery ctDNA levels have a higher risk to recur than those with undetectable levels [32,33]. In the same line, increments in ctDNA or CTCs levels have been associated with disease progression of metastatic lung and breast cancer patients, even before the confirmation of progression by radiological assessment [34][35][36][37]. Additionally, liquid biopsy assessment has a clear role for monitoring and characterizing the resistance to targeted therapies as many works have demonstrated in the last years in the context of hormone therapy in breast cancer patients and anti-EGFR strategies in mCRC or immunotherapy in NSCLC [38][39][40].…”
Section: Liquid Biopsy For Personalized Oncologymentioning
confidence: 97%